1989
DOI: 10.1111/j.1530-0277.1989.tb00420.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Cortical Morphology and Behavior in Rats Following Acute Prenatal Ethanol Exposure

Abstract: Cerebral cortical morphology and early motor development were evaluated in offspring from ethanol-exposed mothers, pairfed control mothers and ad libitum control rats. Ethanol-exposed rats received a total dose of 18 g/kg of ethanol by intubation on gestational Days 14 and 15, a critical period of development of the cerebral cortex. Pairfed control mothers received isocaloric sucrose on gestational Days 14 and 15 and were pairfed to ethanol-exposed animals from gestational Day 12 through gestational Day 20. Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Like Zhou et al (2011) we found thinner cortex in right superior parietal and middle temporal fusiform, calcarine, and lingual gyri. These findings are also consistent with the animal studies showing thinner cortex in alcohol-exposed animals relative to controls (Miller and Dow-Edwards 1988;Norton et al 1988;Kotkoskie and Norton 1989;Leigland et al 2013). Previous studies of cortical thickness in FASD have assessed samples that included both preadolescent and adolescent subjects.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Like Zhou et al (2011) we found thinner cortex in right superior parietal and middle temporal fusiform, calcarine, and lingual gyri. These findings are also consistent with the animal studies showing thinner cortex in alcohol-exposed animals relative to controls (Miller and Dow-Edwards 1988;Norton et al 1988;Kotkoskie and Norton 1989;Leigland et al 2013). Previous studies of cortical thickness in FASD have assessed samples that included both preadolescent and adolescent subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Prenatal exposure to teratogens, such as maternal cigarette smoking (Derauf et al 2012;El Marroun et al 2013), cocaine (Liu et al 2013), opiates (Walhovd et al 2007), and organosphate pesticide (Rauh et al 2012) has also been associated with thinner cortex. In animal studies, rats prenatally exposed to alcohol have shown thinner cortex relative to controls (Miller and Dow-Edwards 1988;Norton et al 1988), particularly in layer V (Kotkoskie and Norton 1989), which persists through multiple postnatal time-points (Leigland et al 2013), particularly in primary sensory areas. Similarly, in adults one of the effects of excessive alcohol consumption is a reduction in cortical thickness compared with healthy controls (Durazzo and Tosun 2011;Fortier and Leritz 2011;Momenan et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…During the neurogenic period, alcohol causes a decrease in a variety of neuronal populations including hippocampal CA1 pyramidal cells [102,103,104,105,106,107,108,109,110,111], cerebellar Purkinje cells [112,113,114,115], and cerebral cortical neurons [116,117]. These effects may be caused by both a disruption of neuronal generation when exposure occurs earlier in gestation, and neuronal apoptosis when exposure occurs later in gestation during defined sensitive periods [103,116,118,119,120,121,122]. …”
Section: Abnormal Differentiation In Fasdmentioning
confidence: 99%
“…An early study by Barnes and Walker (37) reported a loss of hippocampal neurons from a second-trimester equivalent alcohol exposure, and significant work from Miller's lab showed alcohol-induced changes in cortical neuronogenesis (38)(39)(40). Others have shown that rats exposure to ethanol over a 2-d window from, G. D.14-15 exhibit an immediate enlargement of the, S.V.Z, suggesting, N.S.C/NPC maturation (41), disorganized cortical architecture at the end of the neuronogenic period (42), and a persistent thinning of lamina V of the rodent cerebral cortex (43), suggesting that the effects of second-trimester ethanol exposure are persistent.…”
Section: Effects Of Alcohol During Brain Growth and Developmentmentioning
confidence: 99%